THE PRACTICAL SENSE OF INTERRELIGIOUS HARMONY: SOCIAL DYNAMICS IN THE RUWATAN DESA TRADITION IN LUBUK SEBERUK VILLAGE - Ismail; Rahmat Saehu; Nugroho, Novi Dwi; Rabitha, Daniel (Penamas, 2025)
Indonesia’s cultural diversity is both a source of national wealth and a potential ground for intergroup conflict. This study highlights the practice of interreligious harmony in Lubuk Seberuk Village, a community known for its religious and cultural pluralism. Employing a qualitative case study approach, data were collected through in-depth interviews and analyzed using an interactive interpretive model. The findings indicate that harmony is sustained through a collective habitus embedded in everyday cultural practices. The Ruwatan Desa ritual plays a pivotal role as a space for social integration. Beyond its religious symbolism, this ritual reinforces trust, mutual recognition, and solidarity among interfaith communities. It reflects Bourdieu’s concept of sens pratique, where individuals instinctively enact dispositions aligned with an ethos of harmony—not as a result of rational deliberation, but as an outcome of cultural memory and ongoing social interaction. The Ruwatan Desa demonstrates that local traditions can serve as effective instruments for fostering peace and interreligious coexistence in multicultural societies.